Prereplication complex proteins get caught moonlighting. - Hilary A Coller (PLoS Biology)
In this issue of PLOS Biology, Lattmann and colleagues report a new function for proteins of the DNA prereplication complex promoting the anchor cell to invade through the basement membrane and initiate vulval development in Caenorhabditis elegans.